2015
DOI: 10.3390/s150407294
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Software Architecture Based on Confident HCI for the Deployment of Sensitive Services in Smart Homes

Abstract: Smart spaces foster the development of natural and appropriate forms of human-computer interaction by taking advantage of home customization. The interaction potential of the Smart Home, which is a special type of smart space, is of particular interest in fields in which the acceptance of new technologies is limited and restrictive. The integration of smart home design patterns with sensitive solutions can increase user acceptance. In this paper, we present the main challenges that have been identified in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The conceptualization found in this paper is useful when dealing with the software architectural requirements, although it is not easily transferable to a low-level design made by developers. For their part, Vega et al [ 58 ] identified the main challenges in the development of services based on smart environments (considered as a generalization of SH) and proposed an architecture to deal with these. The proposed architecture is based on the model-view controller paradigm commonly used in programming.…”
Section: Smart Home Projects and Applicationsmentioning
confidence: 99%
“…The conceptualization found in this paper is useful when dealing with the software architectural requirements, although it is not easily transferable to a low-level design made by developers. For their part, Vega et al [ 58 ] identified the main challenges in the development of services based on smart environments (considered as a generalization of SH) and proposed an architecture to deal with these. The proposed architecture is based on the model-view controller paradigm commonly used in programming.…”
Section: Smart Home Projects and Applicationsmentioning
confidence: 99%
“…Although researchers have introduced cheap Smart homes health systems that could potentially reduce the cost of health care, affordability in Smart homes is still a hard task to achieve. Smart homes should be designed to minimise the installation cost of components and to Smart homes allowing the reuse of the smarty space components and objects and consequently reducing the final cost [18]. Smart home devices, such as sensors, system components and system tools, and applications should also reduce the computational time as well as minimising the cost of implementing the system [19].…”
Section: Affordabilitymentioning
confidence: 99%
“…Other studies (Vega-Barbas et al, 2015;Waycott et al, 2014) consider patients as the subject interacting with technology tools for their own healthcare. Waycott et al (2014) conducted a multiple case study with 15 pregnant women with type 1 diabetes and concluded that motivated patients play an active role in aligning such interacting activity systems and adjusting their use of technology tools for their own health management.…”
Section: Table 2 Perspectives Of Using Activity Theory In Is Researchmentioning
confidence: 99%